One Extraordinary Lecturer One Article Indexed Minimum Sinta 3 Program to Improve Writing and Research Skills of Extraordinary Lecturers - Agustina, Ika; Nasrudin, Nasrudin; Sinaga, Rommel; Lubis, Reniwati; Putra, Syahripal (Universitas Pahlawan Tuanku Tambusai, 2023)
This research aims to determine (1) the program